Needs Analysis of Chemistry Content and Context for Metal Casting Technology Competency in Vocational High Schools - Ammar Nurhafitri Ningrum; Sjaeful Anwar; Muhammad Nurul Hana (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
This research investigates the relevance of chemistry content and context for vocational high school students majoring in Metal Casting Technology to bridge the gap between the general science curriculum and practical industrial applications. Employing an evaluative approach, data were gathered through documentation studies, in-depth interviews, and expert reviews at SMK Negeri 4 Kota Sukabumi, and subsequently analyzed using Mayring’s Qualitative Content Analysis (QCA). The findings reveal 16 essential chemistry topics that are highly required by the industry but currently unaccommodated in the curriculum, such as precise material composition control, interfacial chemistry in mold coating, and the influence of alloy composition on metal microstructure. Based on these insights, a contextual teaching material outline was formulated to integrate chemical theory with the practical metal casting industry. The development of adaptive learning modules is crucial for enhancing curriculum alignment and boosting graduate workforce readiness.